Resistive Sensors Based on Self-Assembled Core-Shell Nanoparticles. (16th August 2016) - Baklouti, Linda; Rajoua, Khalil; Favier, Frederic
Abstract : Au@Ag, Au@ZnO and Au@SnO2 nanoparticles were synthetized and then assembled by Langmuir Blodgett technique. The resulting close-packed core-shell nanoparticle monolayers were transferred onto glass chips to fabricate NH3 and H2 resistive sensors. Sensing performances of the as fabricated sensors were evaluated through the resistivity changes in the discontinuous particle assemble. The sensitivity of Au@Ag based sensor was tested towards NH3 while Au@ZnO and Au@SnO2 based sensors were tested under H2 . Assembles of core-shell nanoparticles organized by the Langmuir-Blodgett technique demonstrated attractive sensing performances towards the target gases in extended concentration ranges.